N‐Heterocyclic‐Carbene‐Catalyzed One‐Pot Synthesis of Hydroxamic Esters. Issue 12 (11th September 2013) - Song, Xiaoxiao; Ni, Qijian; Grossmann, André; Enders, Dieter
<x xml:space="preserve">Abstract</x> The honey pot: The NHC‐catalyzed reaction between nitrosobenzenes, aromatic/aliphatic aldehydes, and enals proceeded through an aza‐benzoin‐type reaction and an internal redox esterification to afford hydroxamic esters in good yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>